Current approaches to development of real-time qPCR test-kits - M. I. Doronin; D. V. Mikhalishin; A. V. Sprygin; A. Mazloum; T. V. Zhbanova; K. N. Gruzdev; E. V. Chernyshova (Ветеринария сегодня)
Currently fluorescent quantitative real-time polymerase chain reaction, which is a cutting-edge technology in genetic diagnosis, is used in different areas of molecularbiology. Practicaladvantageofsimplicityaswellascombination of high speed, sensitivityandspecificitymadeitpossibletousethisanalysisfor nucleic acidquantitation. Thepaperpresentsgeneral information andrecommendedrules for thedevelopmentof real-timeqPCR. Thepublication isaimedtoacquaint theresearchersandreviewerswith necessaryrequirementstobefollowedin order toensure high accuracy, reliabilityandtransparencyof theexperiments, correct interpretation andrepeatabilityof thetest results. Currentapproachesaredescribedthatallow obtainingreliableandconsistent resultsbydifferentoperators, at differenttimesandin differentlaboratories. Basicrequirementsforreagentsused, nucleotidesequencesandvalidationmethodsaregiven. In general, thepublication givestheinformation neededtoachievethreeultimategoals: toprovidetheauthorswith abroadrangeoftoolsandrequirementsforthedevelopmentof real-time qPCR based-techniques; togivethepossibilitytothereviewersandeditorsofassessingthequalityofarticlesandguidelines/instructions in accordance with the requiredcriteria; toobtain consistentandreliableresultsof testsperformedusingthis method.